Affinity of plant viral nanoparticle potato virus X (PVX) towards malignant B cells enables cancer drug delivery. (17th June 2020) - Shukla, Sourabh; Roe, Anne Jessica; Liu, Ruifu; Veliz, Frank A.; Commandeur, Ulrich; Wald, David N.; Steinmetz, Nicole F.
Abstract : Plant vital nanoparticle PVX shows a binding affinity towards malignant B cells and traffics to metastatic lymphoma sites in mice challenged with B cell lymphoma, thus enabling NHL-specific drug delivery. Abstract : Non-Hodgkin's B cell lymphomas (NHL) include a diverse set of neoplasms that constitute ∼90% of all lymphomas and the largest subset of blood cancers. While chemotherapy is the first line of treatment, the efficacy of contemporary chemotherapies is hampered by dose-limiting toxicities. Partly due to suboptimal dosing, ∼40% of patients exhibit relapsed or refractory disease. Therefore more efficacious drug delivery systems are urgently needed to improve survival of NHL patients. In this study we demonstrate a new drug delivery platform for NHL based on the plant virus Potato virus X (PVX). We observed a binding affinity of PVX towards malignant B cells. In a metastatic mouse model of NHL, we show that systemically administered PVX home to tissues harboring malignant B cells. When loaded with the chemotherapy monomethyl auristatin (MMAE), the PVX nanocarrier enables effective delivery of MMAE to human B lymphoma cells in a NHL mouse model leading to inhibition of lymphoma growth in vivo and improved survival. Thus, PVX nanoparticle is a promising drug delivery platform for B cell malignancies.